2016
DOI: 10.7326/m16-0461
|View full text |Cite
|
Sign up to set email alerts
|

Management of Gout: A Systematic Review in Support of an American College of Physicians Clinical Practice Guideline

Abstract: Agency for Healthcare Research and Quality. (Protocol registration: http://effectivehealth-care.ahrq.gov/ehc/products/564/1992/Gout-managment-protocol-141103.pdf).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 128 publications
2
49
0
4
Order By: Relevance
“…In addition, those patients with a durable response to pegloticase (with serum urate level <6 mg/dl) have an enduring improvement in all relevant clinical outcomes 29,30 . The ACP Clinical Guidelines Committee decided not to consider the pegloticase clinical trial data because pegloticase was considered an agent unlikely to be prescribed by primary care physicians 44 . Nevertheless, the high level of evidence showing a clear clinical benefit of this highly potent urate-lowering agent should help confirm the therapeutic principle of the treat-to-target ULT approach, already universally adopted by rheumatology guidelines.…”
Section: Clinical Benefits Of Successful Ultmentioning
confidence: 99%
“…In addition, those patients with a durable response to pegloticase (with serum urate level <6 mg/dl) have an enduring improvement in all relevant clinical outcomes 29,30 . The ACP Clinical Guidelines Committee decided not to consider the pegloticase clinical trial data because pegloticase was considered an agent unlikely to be prescribed by primary care physicians 44 . Nevertheless, the high level of evidence showing a clear clinical benefit of this highly potent urate-lowering agent should help confirm the therapeutic principle of the treat-to-target ULT approach, already universally adopted by rheumatology guidelines.…”
Section: Clinical Benefits Of Successful Ultmentioning
confidence: 99%
“…Those who survive SJS/TEN are often left with substantial sequelae of involved organs (e.g., corneal damage and renal insufficiency) [1,7]. The 2016 Agency for Healthcare Research and Quality review of the evidence on gout care has identified an important research gap about how to further minimize the rare but serious adverse events from ULT (e.g., by HLA typing for predisposition) in order to improve the benefit/risk profile of therapy and make more patients eligible for treatment [8]. As such, there is an unmet need to improve risk management and perception of allopurinol safety.…”
Section: Introductionmentioning
confidence: 99%
“…(25) We agree with the authors’ conclusions and support for the use of colchicine, NSAIDs, and glucocorticoids for gout flare management as having a high strength of evidence despite there being few placebo-controlled trials (none for glucocorticoids) because of “the known physiology of gout,” and “that symptoms arise from an inflammatory reaction to the deposition of urate crystals, which occurs when serum uric acid rises above its saturation point in blood”. (4) The authors also acknowledge evidence that urate-lowering therapy (ULT) reduces serum urate, which is a strong predictor of flares, and data from open-label extension studies of ULT trials support an association between lower serum urate levels and lower risk of gout flares. It is therefore puzzling that the strength of evidence for monitoring serum urate, a prerequisite to ensuring adequate ULT dosing, is judged to be low.…”
mentioning
confidence: 95%